Phenological Sensitivity of Two Maize Cultivars to Trinexapac-Ethyl - MENDES FAGHERAZZI,M. (2018)
ABSTRACT: In Brazilian agriculture there are few reports on trinexapac-ethyl (TE) effects on maize plant lodging management. This study aimed to evaluate the effects of sequential application of TE sprayed on different plant growth stages of maize using the simple hybrid P30F53HR and the variety SCS 154 Fortuna. Experiments were carried out in a greenhouse in the 2013 and 2014 harvests. Plants were grown singly in 5L pots filled with 75% soil and 25% substrate. The experimental design was a randomized complete block with four replications. The following treatments were performed: (T1) control (no application of growth retardant); (T2) application at V2 (100 g a.i. ha-1); (T3) sequential application of 100 g a.i. ha-1 at V2 plus V3; (T4) sequential application of 100 g a.i. ha-1 at V2+V3+V4; (T5) single application of 300 g a.i. ha-1 at V4; (T6) sequential application of 100 g a.i. ha-1 at V2+V3+V4+V5; (T7) sequential application of 100 g a.i. ha-1 at V2+V3+V4+V5+V6 and (T8) sequential application of 100 g a.i. ha-1 at V2+V3+V4+V5+V6+V7. The some morphological characteristics of the two maize genotypes changed in response to TE treatment. From stage V4 onwards, maize plant height showed signs of sensitivity to the growth retardant. Plants in T8 (TE applied over V2 to V7) were more sensitive to TE with over 45% reduction in plant height compared with application T7 (applied from V2 to V6). This response was similar in both maize genotypes, thus indicating that plants are highly sensitive to TE after the V6 stage.